Cobalt‐Catalyzed Diastereo‐ and Enantioselective Hydroalkenylation of Cyclopropenes with Alkenylboronic Acids. (3rd July 2019) - Zhang, Haiyan; Huang, Wei; Wang, Tongtong; Meng, Fanke
Abstract: Catalytic diastereo‐ and enantioselective hydroalkenylation of 3, 3‐disubstituted cyclopropenes with readily accessible alkenylboronic acids, promoted by a chiral phosphine/Co complex, is presented. Such a process constitutes the unprecedented and direct introduction of a wide range of alkenyl groups onto the cyclopropane motif to afford multisubstituted cyclopropanes in up to 95 % yield with greater than 95:5 d.r. and 99:1 e.r. Functionalization of the products delivered enantioenriched cyclopropanes that are otherwise difficult to access. Abstract : Zur Einführung : Ein neues Verfahren zur hocheffizienten, diastereo‐ und enantioselektiven Hydroalkenylierung von Cyclopropenen mit einem leicht zugänglichen Cobalt‐Katalysator wurde entwickelt. Dieses Protokoll stellt den ersten Ansatz für die Einführung eines breiten Spektrums von Alkenyleinheiten an einen Cyclopropanring dar.